(untitled) (Czech Journal of International Relations, 2002)
Possibly the most fundamental and irreversible shift to come with the reform process in China has been the breaking down of the hermetically sealed and egocentric state economic system. The pre-reform status quo was the legacy of an economic and cultural isolationism dating back to the Ming dynasty (1368-1644). In Maoist times, China was a nationalistic continuation of its own imperial tradition, redefined with the help of some borrowings from Marxist-Leninist ideology. It was only the elite reformers after 1978 who sparked market reforms, opened the country up to foreign capital, and appreciated the benefits of foreign trade in modern economics. However not even this change of orientation toward the outside world and the virtual elimination of Marxist thought led the Chinese to abandon their concept of national cultural identity, which is even reflected in the economy. On the surface it appears that the PRC is an economically open state, as shown by macroeconomic indicators and the rhetoric of Chinese economic diplomacy. In practice, however, this openness is at best debatable and carries with it unique features deeply rooted in the Chinese social system and traditions. China has discovered ways to coexist with the global economic community and is gradually fortifying its position without detriment to its security or political structure. This paper will attempt to map the parallels between the dynastic era and the present in the reserved Chinese approach to opening its economy. Modern China primarily exploits economic ties with the outside world to serve its own interests, but if it plays by the rules of the game of globalization it will put itself at the mercy of forces beyond its own control. Therefore, by opening the economy China is subjecting itself to a number of risks that the previous Maoist phase of Communist dictatorship had temporarily eliminated. The entrance of the PRC into the World Trade Organization signifies another step on its path to modernity, but this comes at the price of social and possibly litical schisms within the state. Further expansion of economic cooperation with the outside world will lead to a breaking down of cultural barriers and an internationalization of the legal and administrative customs, which have heretofore kept China isolated.